Free Cash Flow of Telecommunications Companies in Indonesia - Amran Manurung; Adler Haymans Manurung; Gerry Manurung; Lukman Hakim Sangapan; Gerson Manurung; Jerry Marmen Simanjuntak (Universitas Warmadewa, 2025)
The study aims to investigate the variables that affect the cash flow of telecommunications companies on the Indonesia Stock Exchange. This study uses annual data from 2016 to 2024 and a panel data model. The results of this study state that the Company's fundamental factors are represented by the Company's investment value and the oil price and interest rate variables, and the COVID-19 period significantly affect the Company's Net Cash Flow. The Company's management must manage these internal and external factors so that the Company's net cash flow is controlled.